Using Needs Assessment to Understand Continuing Disability in Patients with Enduring Mental Illness. Implications for Considerations of Service Development - Middleton, Hugh; Adeniran, Richard; Brewin, Chris R.; Brady, Carol; Duggan, Conor; Hopkins, Nigel; Raleigh, Kay; Walton, Mark (Routledge, 2002)
Particular strengths of the MRC Needs for Care Assessment Schedule have been used to investigate the treatment status of patients with persistent psychiatric disability in ways that other needs assessment tools are unable to. One hundred and seventy-nine such patients from three settings; a private sector psychiatric hospital, two public sector day hospitals situated in the same town, and a high security hospital, were found to have a high level of need. Although there were differences between settings, overall these needs were well met in all three. The high level of persistent disability found amongst these patients could not be attributed to failure on the part of those treating them to use the best available methods, or to failures to comply or engage with treatment on the patient's part. In some two thirds of instances persistent disability was best explained by the fact that even the most suitable available treatments have to be considered only partially effective.